Expanding the potentialities of standard dilution analysis: Determination of ethanol in gasoline by Raman spectroscopy - Fortunato, Felipe M. [UNESP]; Vieira, Alan L. [UNESP]; Gomes Neto, José A. [UNESP]; Donati, George L.; Jones, Bradley T. (Elsevier, 2017)
This work describes the application of standard dilution analysis (SDA) in Raman spectroscopy, demonstrating the versatility of this new calibration method. A flow system (FA) was developed for ethanol determination in gasoline employing liquid-liquid extraction (LLE) and acetone as the internal standard (IS). Applying LLE eliminated the intense fluorescence background, allowing for ethanol determination using a portable 785-nm-laser Raman system. The SDA-LLE-FA method was applied to commercial gasoline samples and the results were compared with values obtained using the ABNT NBR 13992 reference method. No statistically significant differences were observed for ethanol concentrations determined using the two methods (paired t-test at the 95% confidence level). SDA's accuracy was also evaluated by comparing results from analyses using the same LLE-FA system combined with the traditional calibration methods of matrix matching (MM), standard additions (SA) and internal standardization (IS). Recoveries from spike experiments were in 98.6–104.1% (SDA-LLE-FA), 94.7–171.1% (ABNT NBR 13992), 106.8–114.1% (MM-LLE-FA), 103.7–108.4% (IS-LLE-FA), and 114.7–125.8% (SA-LLE-FA) range. The relative standard deviation (RSD, n = 12, 25.5% v/v− 1 ethanol in gasoline), limits of detection and quantification calculated for the SDA-LLE-FA method were 2%, 0.5% and 1.8% (v/v− 1), respectively.
Keywords: Ethanol determination; Gasoline analysis; Raman spectroscopy; Standard dilution analysis